'Cinema: Today's Theatre' – Images from the 1914 Cologne Rose Monday Parade. Issue 2 (3rd July 2021) - Grimm, Friederike
ABSTRACT: A carnival float in the 1914 Cologne Rose Monday parade was designed under the slogan 'Theatre Then and Now'. The float depicted a cinema under the headline 'The Theatre of Today', pointing out that the film industry was encroaching on actors, authors and topics of the classical legitimate theatre. While the cinema sector was booming in the city, the Cologne Schauspielhaus (Cologne Theatre) was suffering a severe decline in audience attendance. The painted draft of the carnival float illustrates in detail the discrepancy between cinema and legitimate theatre and what they offered its audiences: long feature films for high entrance fees versus free car rides and free buffet to lure audiences into classical Greek tragedies. The Cologne carnival float commented in a caricaturing way on how the cinema attained sold-out houses with its propositions, while the legitimate theatre remained empty.